작부형태가 보리의 토양전염성 Bymovirus 발생과 매개균(Polymyxa graminis)의 밀도 변화에 미치는 영향 - 박종철(Jong-Chul Park); 노태환(Tae-Hwan Noh); 김미정(Mi-Jung Kim); 이상복(Sang-Bok Lee); 박철수(Chul-Soo Park); 강천식(Chun-Sik Kang); 이정준(Jung-Joon Lee); 김태수(Tae-Soo Kim) (Sigmulbyeong yeon'gu, 2010)
In this study, changes in virus disease occurrence and yield were monitored in conventional cropping system(rice-barley) and soybean-barley double cropping system in virus-prone area for 5 years. Also, changes in the density of Polymyxa graminis, a fungal vector, was investigated. In assay tests, mixed infection of Barley yellow mosaic virus (BaYMV) and Barley mild mosaic virus (BaMMV) was observed. Disease severity was in the range of 7~9 in conventional cropping system. In continuous cropping of soybean-barley and 3-yearfallow land, disease severity also was around 7. However, disease severity was reduced to medium level (5) when barley cultivation was paused for one or two years in soybean-barley cropping. When barley cultivation was paused for a year, the density of P. graminis, a fungal vector for BaYMV and BaMMV, reduced in barley root and soil. Similarly, barley growth was also enhanced by adopting fallow seasons. Compared with the fifth year of conventional cropping, the number of tillers per $m^2$ was increased by 158 when barley cultivation was paused for an year in soybean-barley cropping. When soybean and barley were cultivated continuously or complete fallow period was extended to three years, plant height and the number of tillers of barley were decreased. Yield components of barley in soybean-barley cropping were superior to those in rice-barley cropping. Compared with the fifth year of conventional cropping and soybean-barley cropping, culm length of barley was 1.3~2.3 cm higher and the number of tillers per $m^2$ was 36~90 higher when barley cultivation was paused for one or two years. However, those in continuous cropping of soybean-barley and 3-year-fallow land were lower compared with conventional cropping. Similarly, yield was increased when barley cultivation was paused for one or two years in the third, forth, and fifth years when compared with conventional cropping. 보리바이러스 발생 상습 논에서 관행(벼+보리)과 콩+보리의 작부체계가 보리의 바이러스병 발생과 수량에 미치는 영향을 5개년간 조사하였고, 윤작과 바이러스 매개균(Polymyxa graminis)의 밀도 변화를 검정하였다. 보리 감염 바이러스 종류를 검정한 결과 Barley yellow mosaic virus(BaYMV)와 Barley mild mosaic virus(BaMMV)가 혼합감염 되어 나타났다. 발병정도는 관행에서는 4년차를 제외하고는 7~9로 조사되었다. 반면 콩+보리 연작이나 3년 동안 휴경한 경우는 발병정도가 7정도로 관행과 비슷한 결과를 보였다. 콩+벼 작부체계 중에서 보리를 1년 또는 2년(1년/2년) 휴경하면서 콩을 재배한 경우 발병정도가 중 정도(5)로 감소하는 결과를 보였다. 작부형태에 따른 BaYMV와 BaMMV의 매개균인 P. graminis의 보리 뿌리와 토양 중 밀도 변화를 조사하였다. 보리를 1년 휴경한 처리에서 보리 뿌리와 토양 중 매개균의 밀도가 가장 낮아졌다. 콩을 재배하면서 보리를 1년 휴경한 처리에서 5년차에는 관행에 비해 초장은 비슷하였으나, 경수는 158개/$m^2$ 많아 생육이 좋은 결과를 보였다. 콩과 보리를 연작하거나 3년간 보리와 콩을 재배하지 않고 휴경한 경우에는 관행에 비해 초장이나 경수 등 생육이 저조한 결과를 보였다. 수확기에 간장 등 수량 구성요소가 관행에 비해 보리+콩의 윤작처리에서 좋은 경향을 보여 콩과의 윤작 처리가 수량에도 영향을 미친 것으로 나타났다. 간장은 보리를 1년/2년 휴경한 처리에서 5년차에 관행과 보리+콩 연작 처리에 비해 1.3~2.8 cm 컸고, 수수도 36~90개/$m^2$ 많게 조사되었다. 그러나 콩+보리 연작이나 3년간 휴경한 처리에서는 관행에 비해 낮게 조사되었다. 수량성에서도 보리를 1년/2년 휴경한 처리에서는 3년차, 4년차, 5년차에서 모두 관행에 비해 수량이 많아지는 결과를 보였다.